2015
DOI: 10.1103/physrevlett.114.097002
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Pressure Structural Quantum Critical Point in the Phase Diagram of(CaxSr1x)

Abstract: The quasi-skutterudite superconductor Sr3Rh4Sn13 features a pronounced anomaly in electrical resistivity at T * ∼138 K. We show that the anomaly is caused by a second-order structural transition, which can be tuned to 0 K by applying physical pressure and chemical pressure via the substitution of Ca for Sr. A broad superconducting dome is centred around the structural quantum critical point. Detailed analysis of the tuning parameter dependence of T * as well as insights from lattice dynamics calculations stron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 35 publications
8
111
2
Order By: Relevance
“…Recently, it has been reported that the series (Ca 1−x ,Sr x ) 3 Rh 4 Sn 13 has a very similar phase diagram with a quantum critical point which should appear at ambient pressure if the Ca fraction is 0.9 [15]. This opens the possibility to study the interplay of superconductivity, CDW and quantum criticality over a broader interval of pressures up and beyond the region where superconductivity is strongest and the critical temperature reaches its maximum.…”
Section: Phase Diagrams and Uemura Plotmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been reported that the series (Ca 1−x ,Sr x ) 3 Rh 4 Sn 13 has a very similar phase diagram with a quantum critical point which should appear at ambient pressure if the Ca fraction is 0.9 [15]. This opens the possibility to study the interplay of superconductivity, CDW and quantum criticality over a broader interval of pressures up and beyond the region where superconductivity is strongest and the critical temperature reaches its maximum.…”
Section: Phase Diagrams and Uemura Plotmentioning
confidence: 99%
“…The vicinity to unconventional superconductors is possibly related to the competing CDW state or to the presence of a quantum phase transition. Remarkably the investigated system is placed in the Uemura plot close to 7 V 3 Si, another phonon-mediated superconductor with a nearby structural instability.Recently, it has been reported that the series (Ca 1−x ,Sr x ) 3 Rh 4 Sn 13 has a very similar phase diagram with a quantum critical point which should appear at ambient pressure if the Ca fraction is 0.9 [15]. This opens the possibility to study the interplay of superconductivity, CDW and quantum criticality over a broader interval of pressures up and beyond the region where superconductivity is strongest and the critical temperature reaches its maximum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Refs. 14,15 ) as a structural transition from simple cubic to I43d bcc structure, involving crystallographic cell doubling. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Superconducting stannides [1,2] with stoichiometry A 3 T 4 Sn 13 (A = La, Sr, Ca and T = Co, Rh, Ir) have received a renewed attention owing to the discovery of a structural transition that can be tuned to 0 K [3][4][5]. In Sr 3 Ir 4 Sn 13 and Sr 3 Rh 4 Sn 13 , the structural transition occurs at T * 147 [3,6] and 138 K [4,7], respectively.…”
Section: Introductionmentioning
confidence: 99%